Analysis Of the Influence of Brand Image, Trust, E-Service Quality, and Loyalty Program on Customer Satisfaction and Customer Loyalty on E-Wallet Usage - Pramono, Yogi; Bramantyo, Mahardian Ardhi; Syukur, Muhammad; Dewabroto, Wisnu Sakti; Gunadi, Willy (The International Journal of Accounting and Business Society, 2023)
Purpose — to discover the factors that influence the level of loyalty of e-wallet service users (customer loyalty) when using e-wallet services in Indonesia. Design/methodology/approach—This research uses primary data sources, namely survey data taken using questionnaires made in online media. The questionnaires were distributed to respondents who are active users of e-wallet payment channels via WhatsApp, social media, and personal and group networks. Findings — independent variables significantly affect customer satisfaction: e-service quality, trust, and brand image. The independent variables significantly affecting customer loyalty are e-service quality and customer satisfaction. The other independent variables, namely the loyalty program, have no significant effect on customer satisfaction, and the variables of trust and brand image do not directly and significantly affect customer loyalty of e-wallet users in Indonesia as a mediating variable, customer satisfaction is considered to be a mediating variable between brand image and customer loyalty. However, customer satisfaction cannot be a mediating variable between e-service quality, loyalty, and loyalty programs. Practical implications —     The results of this study can provide a managerial basis for e-wallet services in Indonesia to improve its strategy for increasing customer loyalty to using e-wallet services in Indonesia. Originality/value — This research provides evidence that without any current program, customer loyalty is very high, e-wallet customers have 100% trust both when depositing funds in the e-wallet, the confidentiality of the data provided, as well as other legal aspects that can affect when using e-wallets. -wallets. Therefore, the company should continue to ensure security from a financial perspective and data from internal and external disturbances that will disrupt the company's operations. Paper type — Quantitative Research (Primary)